Glucose-Dependent Insulinotropic Polypeptide Stimulates Osteopontin Expression in the Vasculature via Endothelin-1 and CREB - Berglund, Lisa M.; Lyssenko, Valeriya; Ladenvall, Claes; Kotova, Olga; Edsfeldt, Andreas; Pilgaard, Kasper; Alkayyali, Sami; Brøns, Charlotte; Forsblom, Carol; Jonsson, Anna; Zetterqvist, Anna V.; Nitulescu, Mihaela; et al. (Diabetes (New York, N.Y.), 2016)
Glucose-dependent insulinotropic polypeptide (GIP) is an incretin hormone with extrapancreatic effects beyond glycemic control. Here we demonstrate unexpected effects of GIP signaling in the vasculature. GIP induces the expression of the proatherogenic cytokine osteopontin (OPN) in mouse arteries via local release of endothelin-1 and activation of CREB. Infusion of GIP increases plasma OPN concentrations in healthy individuals. Plasma endothelin-1 and OPN concentrations are positively correlated in patients with critical limb ischemia. Fasting GIP concentrations are higher in individuals with a history of cardiovascular disease (myocardial infarction, stroke) when compared with control subjects. GIP receptor (GIPR) and OPN mRNA levels are higher in carotid endarterectomies from patients with symptoms (stroke, transient ischemic attacks, amaurosis fugax) than in asymptomatic patients, and expression associates with parameters that are characteristic of unstable and inflammatory plaques (increased lipid accumulation, macrophage infiltration, and reduced smooth muscle cell content). While GIPR expression is predominantly endothelial in healthy arteries from humans, mice, rats, and pigs, remarkable upregulation is observed in endothelial and smooth muscle cells upon culture conditions, yielding a “vascular disease–like” phenotype. Moreover, the common variant rs10423928 in the GIPR gene is associated with increased risk of stroke in patients with type 2 diabetes.